Pengaruh Kepemimpinan Transformasional Dan Pengembangan Karir Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada PT. Alfa Scorpii Marelan) - Nicholas Ananta Nasution; Siti Mujiatin (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research is research conducted to determine the influence of transformational leadership and career development on employee performance which is mediated by employee job satisfaction at PT. Alfa Scorpi Marelan. This research uses a quantitative approach with primary data sources obtained from distributing questionnaires. The sampling technique in this research used a purposive sampling technique, with a total of 47 respondents as objects. The analysis carried out in this research includes path analysis using the PLS application. Based on the research results, it was concluded that transformational leadership influences job satisfaction among PT Alfa Scorpi Marelan employees, career development influences job satisfaction among PT Alfa Scorpi Marelan employees, transformational leadership influences employee performance among PTAlfa Scorpi Marelan employees, career development influences performance. employees in PT Alfa Scorpi Marelan employees, Job satisfactioninfluences employee performance in PT Alfa Scorpi Marelan employees, Job satisfaction does not mediate the influence of transformationalleadership on employee performance in PT Alfa Scorpi Marelan employees, Job satisfaction mediates the influence of careerdevelopment in employee performance in PT Alfa Scorpi Marelan employees Alfa Scorpi Marelan Keywords: Transformational Leadership, Career Development, Employee Performance and Employee Job Satisfaction